Effect of Preheating Process and V Groove Type on the Tensile and Metallography Test of ASTM A53 with A36 Weld Joint Using FCAW Method - Pratikno, Herman; Baredwan, Abdullah Husin; Dhanista, Wimala Lalitya (International Journal of Offshore and Coastal Engineering (IJOCE), 2022)
Steel is a metal material that is often used in the maritime industry due to its availability and weldability. ASTM A53 steel is a low carbon steel commonly used for piping applications. ASTM A36 steel is a low carbon steel commonly used for offshore buildings. This study aims to determine the influence of preheat temperature and V groove type on bend resistance of A53 and A36 weld joint using FCAW (Flux Cored Arc Welding) method. The preheat temperature used are 100°C and 150°C with groove type variations used were single V groove and double V groove. The type of protective gas used is 100% CO2. The results of tensile strength test showed that in the welding process in this study, specimen with preheat temperature of 150°C and double V-Groove shape has the strongest tensile strength, with HAZ width of 3.91 mm, ferrite phase percentage of 58.08%, and pearlite phase percentage of 41.92%.